Self-assessment in vet and higher education: links and further developments - Evangelista, Laura; Fonzo, Concetta (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Despite the already existing self-assessment methodologies and tools in place, Education systems need to further invest in quality assurance measures that can guarantee a quality culture. Quality Assurance Frameworks and, more specifically, quality criteria and indicators are increasingly important for all Education providers, and Education authorities as well. The overlapping and redundancy of self- assessment tools and methods in different education and training settings created the condition for an integrated approach that can provide synergies among different systems and a solid base for further implementations and improvements. The paper reports a critical review of quality assurance measures and instruments already existing and used by both the Vocational Education and Training and the Higher Education systems in Europe. Moreover, the research results of a national experimentation will be illustrated to show how the European Peer Review methodology can be considered an agile method for different learning settings since it adapts swiftly to diverse training and education needs and provides quality learning opportunities for those who use it. Finally, the paper places a strong focus on the increased flexibility of the European Quality Assurance for Vocational Education and Training (so-called EQAVET) Framework and other EU quality assurance tools, reinforcing the idea to further explore opportunities for their adaptation to enhance quality and guarantee a continuing improvement of measures in line also with the digital readiness required by the technological revolution and the digital transition that affect the different systems – from School to Higher Education.